Natural Antibacterial and Antivirulence Alkaloids From Macleaya cordata Against Methicillin-Resistant Staphylococcus aureus - Liu, Zhi-Hai; Wang, Wei-Mei; Zhang, Zhen; Sun, Liang; Wu, Shuai-Cheng (Frontiers in Pharmacology, 2022)
The emergence and spread of antibiotic-resistant bacteria, such as methicillin-resistant Staphylococcus aureus (MRSA), underly the urgent need to develop novel antibacterial drugs. Macleaya cordata, a traditional medicinal plant, has been widely used in livestock animals, plants, and humans. Alkaloids are the primary bioactive compounds of Macleaya cordata and exhibit antibacterial, antiinflammatory, and antioxidant activities. Nevertheless, the antibacterial compounds and mode of action of Macleaya cordata remain unclear. In the present study, we investigated the antibacterial activity and mode of action of alkaloids from Macleaya cordata. Sanguinarine, 6-ethoxysanguinarine (6-ES), 6-methoxydihydrosanguinarine (6-MS), chelerythrine (CH), and dihydrochelerythrine (DICH) exhibited good antibacterial activity against gram-positive bacteria, including MRSA. 6-ES rapidly killed MRSA, possibly by interfering with membrane and metabolic functions including ROS production by targeting the membrane and FtsZ in S. aureus. Additionally, 6-ES directly suppressed the hemolytic activity of a-hemolysin, alleviated inflammatory responses, and eliminated intracellular MRSA, as well as displayed low development of drug resistance, in vitro. Finally, a 6-ES-loaded thermosensitive hydrogel promoted wound healing in mice infected with MRSA. These results supported 6-ES as a novel potential candidate or leading compound with antibacterial, antivirulence, and host immunomodulatory activities in fighting against bacterial infections.